Psoriasis vulgaris patient with psoriatic arthritis managed with interleukin-17A inhibitor: Balancing benefits and adverse effects - Utama, Wina S.; Lestari, Wahyu; Hajar, Sitti; Sylvawani, Mahriani; Ismida, Fitri D.; Akele, Richard Y. (Narra Sains Indonesia, 2024)
Psoriasis vulgaris is a significant health problem and up to 30% of the patients are most likely to develop psoriatic arthritis. Secukinumab, an interleukin-17A (IL-17A) inhibitor, is used to treat patients with moderate-to-severe plaques associated with psoriatic arthritis. The aim of this case report was to highlight the efficacy of secukinumab treatment in a patient with both psoriasis vulgaris and psoriatic arthritis focusing the how to balance the benefits and adverse effects. A 36-year-old female came to Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia with chief complaint of itchy and scaly red plaques almost all over the body. The patient also experienced pain in both knees, both ankle joints and index finger as well as thumb in the right hand in the last year. The patient was diagnosed with psoriasis vulgaris and psoriatic arthritis, then treated with phototherapy and 15 mg of oral methotrexate each week for four weeks. Due to no improvement of the initial treatment, the patient received emollient and secukinumab at a dose of 300 mg/week subcutaneously for five weeks. The lesions began to disappear and the joint pain began to relieve. Secukinumab therapy was continued with a dose of 300 mg/month for six months. However, after six months, the patient complained of acnes appeared on the face. Therefore, the maintenance dose of secukinumab was decreased to 150 mg/month. After the reduced maintenance therapy was given, the patient came back with no complained of acnes. The erythematous plaques on trunk, back, arms and legs have subsided, as well as the joint pain. This case highlights that in a moderate-to-severe psoriasis associated with psoriatic arthritis, secukinumab is highly effective. However, since the potential adverse effects, education and regular follow-up are needed to analyze the success of the treatment and to be able to manage the adverse effects.